PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA KARTU KATA PADA SISWA SD NEGERI 002 PASARIBU - Yunistita, Yunistita; Sembiring, Asti Puspita Br (Unversitas Katolik Santo Thomas, 2025)
This research was conducted at elementary school UPT SDN 002 Pasaribu, Humbang Hasundutan Regency. The problem in this study is about students' difficulties in reading the beginning which can affect student learning outcomes. The purpose of this study was to determine the implementation of learning and improve students' beginning reading skills in class II UPT SDN 002 Pasaribu, Humbang Hasudutan Regency. This type of research is Classroom Action Research (PTK). The subjects of this study were 28 second grade students, and the object was to improve the ability to read the beginning of Indonesian language by using word card media in second grade students of UPT SDN 002 Pasaribu, Humbang Hasundutan Regency. The data collection techniques used were observation sheets and documentation. The results of the study showed that the implementation of learning using picture word card media with the achievement of completeness in cycle I was in the sufficient category while the achievement of completeness in cycle II was in the good category. The conclusion in this study using picture word card media in early reading in class II UPT SDN 002 Pasaribu, Humbang Hasudutan Regency has increased.